Prevention of Pressure Oscillations in Modeling a Cavitating Acoustic Fluid - B. Klenow; A. Brown (Shock and Vibration)
Cavitation effects play an important role in the UNDEX loading of a structure. For far-field UNDEX, the structural loading is affected by the formation of local and bulk cavitation regions, and the pressure pulses resulting from the closure of the cavitation regions. A common approach to numerically modeling cavitation in far-field underwater explosions is Cavitating Acoustic Finite Elements (CAFE) and more recently Cavitating Acoustic Spectral Elements (CASE). Treatment of cavitation in this manner causes spurious pressure oscillations which must be treated by a numerical damping scheme. The focus of this paper is to investigate the severity of these oscillations on the structural response and a possible improvement to CAFE, based on the original Boris and Book Flux-Corrected Transport algorithm on structured meshes [6], to limit oscillations without the energy loss associated with the current damping schemes.